The Civil Aspects of Bullying Cases Against Children in Educational Institutions - Hanafie, Nurharsya Khaer; Herman, Herman; Gani, Andika Wahyudi; Firmansyah, Firmansyah (International Journal on Advanced Science, Education, and Religion, 2024)
This article reviews the civil aspects of bullying cases against children in educational institutions. This study shows that bullying behavior still exists today, ironically not only by adults but also by children at the elementary school level. For example, Mangkura V Elementary School (SD)where students often bully other students, this happens because of internal and external factors which then become the background for bullying. The type of this study is descriptive analytical, the instruments in the study are interviews and literature reviews and data sources come from stakeholder interviews and critical reading of related literature. The results of the study are that bullying behavior often occurs in Mangkura V Elementary School, with different patterns of both individuals and groups, so it is hoped that the settlement mechanism will prioritize civil aspects, in addition to being able to carry out recovery with compensation, it is also expected to provide a deterrent effect on perpetrators of bullying.